2012
DOI: 10.1111/j.1743-6109.2012.02785.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Higher Fecundity in Female Maternal Relatives of Homosexual Men

Abstract: Introduction Recent evidence suggests that sexually antagonistic genetic factors in the maternal line promote homosexuality in men and fecundity in female relatives. However, it is not clear if and how these genetic factors are phenotypically expressed to simultaneously induce homosexuality in men and increased fecundity in their mothers and maternal aunts. Aims The aim of the present study was to investigate the phenotypic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Speculation has included the possibility that such genes increase sexual attraction to men in both homosexual men and their heterosexual female relatives, leading to increased reproduction in the females (Camperio Ciani et al 2008). An empirical study focusing on female maternal relatives of homosexual men found several personality and self-reported health differences (Camperio Ciani et al 2012); it is unclear if any of the differences were related to increased fecundity. A different possibility, overdominance (male heterozygote advantage) (MacIntyre & Estep, 1993), could conceivably help explain the paradox of autosomal genes for male homosexuality, including our findings of linkage to the pericentromeric region of chromosome 8.…”
Section: Discussionmentioning
confidence: 99%
“…Speculation has included the possibility that such genes increase sexual attraction to men in both homosexual men and their heterosexual female relatives, leading to increased reproduction in the females (Camperio Ciani et al 2008). An empirical study focusing on female maternal relatives of homosexual men found several personality and self-reported health differences (Camperio Ciani et al 2012); it is unclear if any of the differences were related to increased fecundity. A different possibility, overdominance (male heterozygote advantage) (MacIntyre & Estep, 1993), could conceivably help explain the paradox of autosomal genes for male homosexuality, including our findings of linkage to the pericentromeric region of chromosome 8.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that alleles contributing to sexual interest in individuals of the same sex could simultaneously convey other advantages that outweigh the negative consequences of homosexual interest with regard to producing offspring. For instance, there is some empirical evidence that genes coding for homosexuality could increase fecundity in female carriers of the alleles . Sexual orientation in terms of gender can, to some extent, be compared with pedophilia (as a sexual preference in terms of age).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from external phenotypic characteristics and hypergyny, there might be psychological and physiological factors that could potentially explain the elevated fertility previously observed among the female relatives of androphilic males. For example, A. S. Camperio Ciani et al (2012) found that the female kin of androphilic males who had increased fecundity also exhibited fewer pregnancy complications and gynecological disorders.…”
Section: Discussionmentioning
confidence: 99%